GW24-e1760 Localisation of the origin site of outflow tract ventricular arrhythmias by surface electrocardiogram. (1st October 2013) - Shibei, Li; Yaling, Han
Abstract : Objectives: It has been reported that the origin site of idiopathic ventricular arrhythmias from left or right outflow tract (L/RVOT) can be judged from the transition of R/S on precordial lead of surface ECG, but its value still need to be confirmed in more studies. This study reports the relationship between surface ECG and the origin of the premature ventricular contractions (PVCs) or ventricular tachycardia (VT) in a large series. Methods: The ECG characteristics in 207 consecutive patients who underwent radio frequency catheter ablation of LVOT or RVOT origin of VT/PVCs were analysised respectively. All the patients had no significant structural heart diseases. Results: The number of patients whose transition of R/S on precordial leads was before lead V2, in lead V3 and after lead V4 were 18 (47.6 ± 8.8 years old on the average), 75 (45.5 ± 13.1years), and 114 ((42.25 ± 13.69), respectively. In the 18 cases of R/S wave transition before lead V2, LVOT origin was defined in all the patients, with the specificity of 100% and sensitivity of 72.00%. In the 75 cases of R/S wave transition in lead V3, the lead V2 R/S transition during sinus rhythm was earlier than that during PVCs or VT in 66 patients, and RVOT origin was determined in all of them. In the other 9 patients with lead V3 R/S transition, 7 of them had a LVOT origin with a later R/S transition in lead V2 during sinus rhythm other than during PVCs or VT. Therefore, in patients with lead V3 R/S transition, if lead V2 R/S transition during sinus rhythm was later than that during PVCs or VT, the specificity and the sensitivity of LVOT origin were 97.06% and 100% separately. In the 114 cases of R/S transition after (≤) lead V4, RVOT origin was defined in all the patients, with the specificity of 100% and sensitivity of 62.63%. Conclusions: There is a high specificity of identifying the origin of ventricular arrhythmias from LVOT by R/S transition before lead V2, a high specificity and sensitivity of identifying origin from RVOT by R/S transition after lead V4. The specificity and sensitivity are high to define the PVCs or VT origin from LVOT or RVOT by measuring the R/S ratio on lead V2 between sinus rhythm and PVCs.